Mini Tinjauan Literatur Pemanfaatan Software Xfunc untuk Berpikir Komputasi Siswa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to review the potential use of xFunc software in improving junior high school students' computational thinking skills in mathematics learning. The method used is a descriptive literature study by analyzing 10 selected articles from 72 articles searched through Publish or Perish in the period 2019–2024. The results of the study indicate that although it has not been studied much directly, xFunc has features that are relevant to computational thinking components, such as decomposition, algorithms, and visualization of mathematical expressions. These findings recommend the need for further empirical research to optimize the integration of xFunc as an interactive learning medium at the junior high school level.